Use of Complementary and Integrative Methods in the Management of Postoperative Pain: A Narrative Literature Review - Gülcan Dürüst Sakallı; Öykü Kara (Galenos Publishing House, 2022)
Pain is at the top of the common problems experienced by patients in the postoperative period. The use of pharmacological and non-pharmacological methods together is of great importance in the management of postoperative pain. The current multimodal analgesia approach, advances in enhanced recovery after surgery protocols, and the use of safe and low-dose opioids in the management of postoperative pain have made the use of complementary and integrative methods even more important in improving the quality of postoperative pain management. The use of complementary and integrative methods (massage, neuro-linguistic programming, music therapy, laughter therapy, virtual reality distraction, progressive relaxation exercises, hydrotherapy, reiki, reflexology, hot-cold compress, transcutaneous electrical nerve stimulation, acupressure, and aromatherapy) in the management of postoperative pain provides rapid recovery and discharge time, a decrease in the need for analgesics and the frequency and amount of opioid use, and an increase in patient satisfaction, well-being, pain control quality, and quality of life by reducing the patient's pain. It is important for surgical nurses, who have an important role in postoperative pain management, to know the methods of relieving pain and to include non-pharmacological practices that increase the quality of pain management in the treatment and care process of pain. This article presents the most commonly used complementary and integrative methods in postoperative pain management in light of current information.